2000
DOI: 10.1007/s002100000214
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a series of draflazine analogues with equilibrative nucleoside transporters: species differences and transporter subtype selectivity

Abstract: The equilibrative nucleoside transporters of mammalian cells play an important role in the regulation of extracellular adenosine concentrations, and inhibition of these transporters potentiates the biological effects of adenosine. Two subtypes of equilibrative transporters have been defined by their differential sensitivities to inhibition by nitrobenzylthioinosine (NBMPR; es/ENT1, sensitive; ei/ENT2, insensitive). In addition, significant species differences have been noted in es/ENT1 transporter affinity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…This suggests that there are multiple structural determinants for dipyridamole binding to the transporter, and that the mouse transporter shares at least one additional interaction site for dipyridamole with the human transporter that is not found in rENT1. We have also screened a variety of analogues of draflazine and have identified functional groups important for ENT1 versus ENT2 selectivity in the mouse, as well as chemical features that contribute to hENT1 versus mENT1 binding affinity [20,34]. These structure-activity data, in conjunction with the amino acid sequences of mENT1 and mENT2 determined in the present study, will assist in the delineation of the protein domains involved in the binding of draflazine, and other cardioprotective agents, to nucleoside transporters [11,35,36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that there are multiple structural determinants for dipyridamole binding to the transporter, and that the mouse transporter shares at least one additional interaction site for dipyridamole with the human transporter that is not found in rENT1. We have also screened a variety of analogues of draflazine and have identified functional groups important for ENT1 versus ENT2 selectivity in the mouse, as well as chemical features that contribute to hENT1 versus mENT1 binding affinity [20,34]. These structure-activity data, in conjunction with the amino acid sequences of mENT1 and mENT2 determined in the present study, will assist in the delineation of the protein domains involved in the binding of draflazine, and other cardioprotective agents, to nucleoside transporters [11,35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Relative to hENT1, mENT1 was also missing two amino acids (Lys-Gly) from the large central intracellular loop ; however, another mENT1 isoform (mENT1b ; Figure 1 and see below) was also identified in the present study that did not have this particular two-amino-acid deletion. In general, the major differences in ENT1 sequence between species (rat, mouse and human) occurred in the C-terminal half of the large extracellular loop between TM1 and TM2 and in the fifth extracellular loop between TM9 and TM10 ; these differences may contribute to the distinctive affinities of the transporters from the three species for the cardioprotective agents dipyridamole, dilazep and draflazine [21][22][23][24][25][26]34]. In this regard, Sundaram et al [37] have used hENT1\rENT1 chimaeric constructs to identify a region bordered by residues 100 and 231 in hENT1 as being critical for the interaction of dipyridamole and dilazep with the transport protein.…”
Section: Ment1mentioning
confidence: 99%
See 1 more Smart Citation
“…Draflazine, a lidoflazine analog, also exhibits high ENT1 inhibitory activity (IC 50 = 0.28-10 nM). 18 However, NBMPR and the flazine compounds like draflazine are poor candidates for further exploration. NBMPR has immunosuppressive and mutagenic activities deriving from its 6-mercaptopurine metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the rapid uptake of ImmH was facilitated by one of the equilibrative nucleoside transporters (ENTs). ImmH uptake was significantly enhanced in PK15 cells expressing ENT1 or ENT2 compared to ENT-deficient PK15 cells and the uptake of ImmH into CCRF-CEM cells was blocked by incubation with DP, an ENT1 and ENT2 inhibitor 8,22 . Based on ENT expression analysis, our data suggests that ENT1 is predominantly responsible for ImmH uptake in CCRF-CEM cells.…”
Section: Discussionmentioning
confidence: 95%